2014
DOI: 10.1021/jm401853a
|View full text |Cite
|
Sign up to set email alerts
|

Application of ProTide Technology to Gemcitabine: A Successful Approach to Overcome the Key Cancer Resistance Mechanisms Leads to a New Agent (NUC-1031) in Clinical Development

Abstract: Gemcitabine is a nucleoside analogue commonly used in cancer therapy but with limited efficacy due to a high susceptibility to cancer cell resistance. The addition of a phosphoramidate motif to the gemcitabine can protect it against many of the key cancer resistance mechanisms. We have synthesized a series of gemcitabine phosphoramidate prodrugs and screened for cytostatic activity in a range of different tumor cell lines. Among the synthesized compounds, one in particular (NUC-1031, 6f) was shown to be potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
206
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(218 citation statements)
references
References 40 publications
5
206
0
Order By: Relevance
“…However it results in only very modest increases in median life expectancy due to the onset of chemo-resistance. A number of variants on the use of gemcitabine have been explored, including pro-drug approaches and combinations with paclitaxel789. However to date none have shown major improvements in late-stage clinical trials, which contrasts with the advances in treatment seen with a number of other cancer types.…”
mentioning
confidence: 99%
“…However it results in only very modest increases in median life expectancy due to the onset of chemo-resistance. A number of variants on the use of gemcitabine have been explored, including pro-drug approaches and combinations with paclitaxel789. However to date none have shown major improvements in late-stage clinical trials, which contrasts with the advances in treatment seen with a number of other cancer types.…”
mentioning
confidence: 99%
“…A recent strategy to improve the treatment efficiency of gemcitabine have been developed by using the phosphoramidate ProTide approach [217] Slusarczyk et al [217] developed Acelarin (NUC-1031) by addition of a phophoramidate ProTide moiety to gemcitabine which enables: a) passive entry into the cell; b) by-passing of the reliance on transporters; c) reduced reliance on kinases for phosphorylation, and, d) reduced susceptibility to deamination. Acelarin generates high intracellular levels of the active agents and has been well tolerated by the patients [217,218].…”
Section: Emerging Chemotherapeutic Treatmentsmentioning
confidence: 99%
“…Acelarin generates high intracellular levels of the active agents and has been well tolerated by the patients [217,218]. Results from the Phase I/II study showed that Acelarin achieved a remarkable disease control rate of 78% in patients with advanced, rapidly progressing solid tumours, relapsed/refractory on prior chemotherapy, including gemcitabine [218].…”
Section: Emerging Chemotherapeutic Treatmentsmentioning
confidence: 99%
“…N-Acyl-phosphoramidates derivatives of gemcitabine can overcome acquired resistance to gemcitabine caused by deoxycytidine kinase deficiency [186]. Similarly, Mcguigan et al have disclosed NUC-1031, a gemcitabine phosphoramidate prodrug that has shown significant reduction in viability of tumor cells [187]. Zhao et al demonstrated the efficacy of cell penetrable dendrimer as a potential antitumor drug carrier by 5-FU and lysine dendrimer conjugates [188].…”
Section: Prodrug Approach: Analog / Chemical Conjugation For Cancementioning
confidence: 99%